AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 30: PORTRAIT OF THE KHARKOV MATHEMATICIAN, MECHANICAL ENGINEER AND CYBERNETICIST VLADIMIR LOGVINOVICH RVACHEV - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. Description of basic scientific achievements, features of personality and way of life of the known Kharkov mathematician, mechanical engineer and cyberneticist, academician of NAS of Ukraine Rvachev V.L .in the short form is presented. Methodology. Existent scientific approaches for treatment and systematization of mathematical knowledges, modern achievements in area of methods of direct solution of linear (nonlinear) boundary problems of mechanics and mathematical physics with the scope terms of different types for the physical bodies of difficult geometrical form. Methods of historical method at research of development in society of analytical geometry, applied mathematics, classical mechanics and mathematical physics. Results. Short information is resulted about the basic creative and vital stages, and also fundamental scientific achievements of the indicated scientist-mathematician the scientific legacy of which entered in the treasure-house of world mathematical science. Are some personal qualities of this prominent soviet Ukrainian mathematician of the 20-th century, forming scientific school on the mathematical method of R−functions and leaving about itself kind memory for thankful students and descendants. Originality. First taught in 1970-th at the known mathematician of contemporaneity of Rvachev V.L. to bases of the applied mathematics and theory of R−functions by a scientist-electrophysicist from the Kharkov polytechnic institute presented for the wide circle of readers a short scientifically-historical essay about this large scientist-teacher, being based on his scientific labours, published biobibliographic materials and flashbacks of his devoted students-followers about him. Practical value. Scientific popularization of the special physical and mathematical knowledges and distinguished scientific achievements of the known Kharkov scientist-mathematician Rvachev V.L. in area of the applied mathematics, classical mechanics of continuous media, mathematical physics and technical cybernetics.